2023
DOI: 10.1039/d3fo00068k
|View full text |Cite
|
Sign up to set email alerts
|

Maternal supplementation with glycerol monolaurate improves the intestinal health of suckling piglets by inhibiting the NF-κB/MAPK pathways and improving oxidative stability

Abstract: Maternal diet supplemented with 0.1% GML enhanced offspring intestinal oxidative homeostasis and barrier function, and attenuated offspring intestinal inflammatory response possibly through suppressing the activation of the NF-κB/MAPK pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Glycerol monolaurate (GML) exhibits potent antimicrobial, antiviral, and anti-inflammatory properties, effectively enhancing animal resistance to infections, immunity, and overall health [16]. Research conducted in sows has revealed that both Se and GML could enhance the redox balance, resulting in improved pregnancy outcomes by mitigating risks, such as intrauterine growth restriction, abortion, and infections [17][18][19][20]. Accumulating evidence demonstrates that the gut microbiota composition undergoes modification and reshaping in animals supplemented with Se and GML, implying that the gut microbiota could potentially function as a beneficial mechanism for enhancing reproductive health [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Glycerol monolaurate (GML) exhibits potent antimicrobial, antiviral, and anti-inflammatory properties, effectively enhancing animal resistance to infections, immunity, and overall health [16]. Research conducted in sows has revealed that both Se and GML could enhance the redox balance, resulting in improved pregnancy outcomes by mitigating risks, such as intrauterine growth restriction, abortion, and infections [17][18][19][20]. Accumulating evidence demonstrates that the gut microbiota composition undergoes modification and reshaping in animals supplemented with Se and GML, implying that the gut microbiota could potentially function as a beneficial mechanism for enhancing reproductive health [21,22].…”
Section: Introductionmentioning
confidence: 99%